2010
DOI: 10.1111/j.1365-2567.2009.03244.x
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐7 promotes the survival of human CD4+ effector/memory T cells by up‐regulating Bcl‐2 proteins and activating the JAK/STAT signalling pathway

Abstract: SummaryInterleukin-7 (IL-7) is a crucial cytokine involved in T-cell survival and development but its signalling in human T cells, particularly in effector/ memory T cells, is poorly documented. In this study, we found that IL-7 protects human CD4 + effector/memory T cells from apoptosis induced upon the absence of stimulation and cytokines. We show that IL-7 upregulates not only Bcl-2 but also Bcl-xL and Mcl-1 as well. Interleukin-7-induced activation of the janus kinase/signal transducer and activator of tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
95
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(102 citation statements)
references
References 53 publications
4
95
1
2
Order By: Relevance
“…A possible explanation for the age-associated proneness to spontaneous apoptosis is the decreases in both IL-7 levels and IL-7 receptor with aging (Kim et al 2006;Kang et al 2004). The IL-7 pathway is necessary for the development and survival of memory T cells by upregulating Bcl-2 pro-survival proteins (Chetoui et al 2010). It would thus be interesting to know whether a training lifestyle can lead to preservation of this pathway, particularly because IL-7 is also secreted by human skeletal muscle cells, and this secretion can be modulated by exercise (Haugen et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation for the age-associated proneness to spontaneous apoptosis is the decreases in both IL-7 levels and IL-7 receptor with aging (Kim et al 2006;Kang et al 2004). The IL-7 pathway is necessary for the development and survival of memory T cells by upregulating Bcl-2 pro-survival proteins (Chetoui et al 2010). It would thus be interesting to know whether a training lifestyle can lead to preservation of this pathway, particularly because IL-7 is also secreted by human skeletal muscle cells, and this secretion can be modulated by exercise (Haugen et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…A more recent report found that IL-7 not only maintained the levels of Mcl-1 but also of Bcl-2 and Bcl-X L , but the analysis there was conducted at 24 h or later of in vitro culture, and therefore secondary effects cannot be judged [25]. Intriguingly, although IL-15 has also been found to stabilise Mcl-1, this effect of IL-15 appears to be conserved between cell types while the effect on Bim is not.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is reasonable to speculate that the induction of the STAT5 pathway by TSLP and common-g chain family cytokines is related to the corticosteroid resistance in NH cells. In CD4 T lymphocytes, the activation of STAT5 by IL-7 upregulates Bcl-2 and Bcl-xL, protecting the cells from apoptosis 40 . Similarly, TSLP decreased the apoptosis of NH cells with a concomitant induction of Bcl-xL and the induction of Bcl-xL was resistant to corticosteroids.…”
Section: Discussionmentioning
confidence: 99%